A Look at the Development of Physics and Its Social Role - KUMAR, Dr. SANJEEV; RAJU, MUDIGONDA NAGA; KUMAR, M SRAVAN; RANI, S SWAPNA (The journal of contemporary issues in business and government, 2019)
This paper analyzes the recent growth in our understanding of physics in general and quantum world in particular focusing on its relevance to our society. Physics touches every aspect of our lives. It involves the study of matter, energy and their interactions. As such, it is one area of science that cuts across all other subjects. Other sciences are reliant on the concepts and techniques developed through physics. Other disciplines — such as chemistry, agriculture, environmental and biological sciences — use the laws of physics to better understand the nature of their own studies. Physics focuses on the general nature of the natural world, generally through a mathematical analysis. Physics is one of the most difficult subjects taught in schools. A number of students are even more daunted with its use of mathematics. In a study done in UK from 1985 to 2006, it was found that there was 41 percent decrease in the number of entries to A-level examinations in sciences. This decreasing trend is similar in other countries. Despite this trend, physics remains an integral part of the educational system. It is through physics that new methodologies were developed that helped improve the quality of life, including things such as automobiles and modern construction.Society’s reliance on technology represents the importance of physics in daily life. Many aspects of modern society would not have been possible without the important scientific discoveries made in the past. These discoveries became the foundation on which current technologies were developed. Discoveries such as magnetism, electricity, conductors and others made modern conveniences, such as television, computers, phones and other business and home technologies possible. Modern means of transportation, such as aircraft and telecommunications, have drawn people across the world closer together — all relying on concepts in physics.In 1999 during the World Conference on Science (WCS), the UNESCO-Physics Action Council considered physics an important factor in developing solutions to both energy and environmental problems. Physics seeks to find alternative solutions to the energy crisis experienced by both first world and developing nations. As physics help the fields of engineering, bio-chemistry and computer science, professionals and scientists develop new ways of harnessing preexisting energy sources and utilizing new ones. In the United Nations Millennium Summit held in 2000, it was recognized that physics and the sciences will play a crucial role in attaining sustainable development. Physics helps in maintaining and developing stable economic growth since it offers new technological advances in the fields of engineering, computer science and even biomedical studies.